MORAL VALUES IN THE MOVIE STAND BY ME DORAEMON 2 - Apriliani, Via (Universitas Pakuan, 2025)
Film is a form of modern literature. It not only acts as a medium of entertainment but also serves as an effective tool for education, conveying meaningful messages, especially to children. This study aims to analyze the moral values present in the film Stand By Me Doraemon 2. The method used is qualitative and descriptive, focusing on story elements such as character portrayals, dialogue, and visuals to understand how moral values are conveyed. The analysis reveals that this movie features various moral values, including (1) self-confidence, demonstrated by Nobita in overcoming his doubts on his wedding day and Doraemon's bravery in facing critical situations, (2) keeping promises, (3) hard work, (4) perseverance, (5) helping others, (6) care and empathy, (7) love and responsibility, (8) true friendship, and (9) respect for parents. Stand By Me Doraemon 2 is an effective medium for teaching individual and social moral values, serving as a clear example of how education applies to everyday life, especially for children and adolescents.